A Case of Widespread Keratosis Pilaris-like eruption Associated with Nilotinib Used for Chronic Myelogenous Leukemia - Bostan, Ecem; Jarbou, Adam; Ersoy Evans, Sibel (Acta Medica, 2022)
Keratosis pilaris is a skin disorder which is characterized by follicular hyperkeratosis. It is most commonly seen in patients with atopic dermatitis and ichthyosis vulgaris. Abnormal keratinization of the hair follicle leads to plugging and bumpy, rough appearance. Upper extensor arms, thighs, buttocks and cheeks are most commonly affected by the disease. Even though keratosis pilaris is associated with autosomal dominant inheritance; it may also be seen as a side effect of various targeted cancer therapies including BRAF and tyrosine kinase inhibitors. Herein, we would like to present a case of keratosis pilaris that had developed secondary to nilotinib treatment.